Capacity Growth of Heterogeneous Cellular Networks. (30th May 2013) - Ling, Jonathan; Chizhik, Dmitry; Chen, Chung Shue; Valenzuela, Reinaldo A.
Abstract: Heterogeneous cellular networks are composed of a mixture of macro and small (pico) cells embedded in the macro network. We assume uniform traffic for simplicity, and study the scaling of area spectral efficiencies (ASEs) as pico densities are increased, optimizing over transmit power and cell association bias. We found that median ASE grows linearly with the number of picos, with a slope as low as one, i.e., only one picocell per macro sector is necessary to double median ASE. The pico must be placed intelligently rather than randomly, and needs only transmit at −20 dB power equivalent isotropic radiated power (EIRP) relative to the macro. The effectiveness of the pico at such low power is due in part to the improvement in area coverage of an omnidirectional versus a three‐sectored antenna. As pico density increases five percentile, signal‐to‐noise and interference ratio (SINR) decreases, causing poor scaling of edge rates. However, cell association bias was found to be an effective means of restoring the otherwise poor scaling of fifth percentile rates. © 2013 Alcatel‐Lucent.